Study of steel EC-181. Dependence of lattice parameter on temperature and Debye-Waller factor - Dineykhan, М.; Sumin, V.V.; Sangaa, D.; Balagurov, А.М.; Aznabaev, D.Т.; Mukhametuly, B. (Recent Contributions to Physics, 2012)
The samples were investigated by the EC-181 thermal neutron diffraction in the temperature range 15-973 K on the IBR-2 reactor (JINR). From the diffraction spectra by the Rietveld method, we calculated the temperature dependence of the lattice parameter, the internal stresses third kind, and Debye-Waller factor of the steel. It was found that at low temperatures the temperature dependence of the lattice parameter in the steel EK-181 (RUSFER EK-181) does not correspond to that in pure iron and binary iron-chromium alloys with 12 and 16% Cr. In addition, the observed broadening of the reflection (200) diffraction spectra were EC-181 and alloy Fe-12Cr, is not observed in the spectra of Fe-16Cr and pure iron.